Biosynthesis of cyclosporins and other natural peptidyl prolyl cis/trans isomerase inhibitors - Lawen, Alfons (Biochimica et biophysica acta, 2015)
Peptidyl-prolyl-cis/trans-isomerases (PPIases) are ubiquitously expressed and have been implicated in a wide range of biological functions. Their inhibition is beneficial in immunosuppression, cancer treatment, treatment of autoimmune diseases, protozoan and viral infections. Three classes of PPIases are known, each class having their own specific inhibitors. This review will cover the present knowledge on the biosynthesis of the natural PPIase inhibitors. These include for the cyclophilins: the cyclosporins, the analogues of peptolide SDZ 214-103 and the sanglifehrins; for the FKBPs: ascomycin, rapamycin and FK506 and for the parvulins the naphtoquinone juglone. Over the last thirty years much progress has been made in understanding PPIase function and the biosynthesis of natural PPIase inhibitors. Non-immunosuppressive analogues were discovered and served as lead compounds for the development of novel antiviral drugs. There are, however, still unsolved questions which deserve further research into this exciting field. As all the major natural inhibitors of the cyclophilins and FKBPs are synthesized by complex non-ribosomal peptide synthetases and/or polyketide synthases, total chemical synthesis is not a viable option. Thus, fully understanding the modular enzyme systems involved in their biosynthesis may help engineering enzymes capable of synthesizing novel PPIase inhibitors with improved functions for a wide range of conditions. This article is part of a Special Issue entitled Proline-directed Foldases: Cell signaling catalysts and drug targets. •Cyclosporin A, a strong immunosuppressant, has also antiviral activity.•Cyclosporin A is synthesized by trans action of 3 enzymes.•Using cyclosporin synthetase, the non-immunosuppressive analogue NIM-811 was obtained.•The antiviral activity of NIM-811 triggered development of many new PPIase inhibitors.•Pathway engineering may yield better compounds to fight HIV and HCV.